Optimization Of Rubber Seed (Hevea Brasiliensis) Drying In Rubber Seed Oil Extraction For Chamois Leather Tanning - Ono Suparno; Ika Amalia Kartika; . Muslich; Gita N. Andayani; Kurnia Sofyan (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Drying is one of the important steps in oil extraction using mechanical pressing. It can decrease oil hydrolysis and increase yield of oil due to the decrease of oil affinity on the material surface and protein coagulation. Therefore, the oil will be released easily from seed in the oil extraction using the hydraulic pressing. Objectives of this research were to determine a combination of temperature and duration of drying of rubber seed prior to oil extraction in order to produce oil with the best yield and physico-chemical properties for chamois leather tanning, and to observe the potency of the rubber seed oil as a leather tanning agent. This research consisted of sortation of rubber seed, rubber seed drying using an oven, oil extraction using a hydraulic pressing, and analysis of physico-chemcal properties of the oil and residue of rubber seed after extracting its oil. Results of the research shows that the higher temperature and duration of rubber seed drying, the higher oil content in residue and colour of the oil, whereas yield, iodine number, acid number, free-fatty acid content of the oil, as well as water content of the rubber seed decreased. Based on the highest of yield and iodine number, the best treatment for the rubber seed drying was drying at 70oC for one hour. This condition resulted in oil with physico-chemical characteristics of oil: yield of 20.52%, colour of 4077 PtCo unit; density of 0.924, viscosity of 160 centipoises, iodine number of 146, acid number of 2.08, FFA of 1.04 %, saponification number of 184.58, and peroxide number of 30.46. The treatment gave oil content in the residue of 9.84 %. The rubber seed oil was potential for substituting fish oil as tanning agent, as it had iodine number of higher than 120.Keywords: drying, rubber seed, oil, oil tanning, tanning agent, chamois leather.